Does Intellectual Property Protection Spur Technological Change - Sunil Kanwar; Robert Evenson (Yale University, Economic Growth Center, 2001)
Of the diverse factors motivating technological change, one factor that has received increasing attention in the recent past has been the protection of intellectual property rights. Given fairly recent changes in the international policy ethos where a regime of stronger intellectual property protection has become a fait accompli for most developing countries, it is of some significance to ask whether more stringent protection of intellectual property does indeed encourage innovation. And this is the question which this paper examines, utilising cross-country panel data on R&D investment, patent protection and other country-specific characteristics spanning the period 1981-1990. The evidence unambiguously indicates the significance of intellectual property rights as incentives for spurring innovation.
Keywords: O34; O31; 330; Intellectual Property Rights; Technological Change; Economic Growth; Technischer Fortschritt; Immaterialgüterrechte; Industrieforschung; Welt